Knowledge and Use of Evidence-Based Practice in Psychology in the Clinical Practice of Brazilian Psychologists: A Cross-Sectional Study - Melnik, Tamara; Sinval, Jorge; Pinho, Vanessa Dordron de; Junior, José Antônio Spencer Hartmann; Oliveira, Margareth da Silva; Lopes, Fernanda Machado (Healthcare (Basel), 2025)
Background/Objectives: The use of scientific evidence for the diagnosis and treatment of mental disorders is crucial for achieving optimal clinical outcomes and providing high-quality care. This study investigates the knowledge, sources of evidence, and attitudes of Brazilian clinical psychologists regarding evidence-based practice in psychology (EBPP) and discusses barriers to its implementation. Methods: A total of 696 Brazilian clinical psychologists participated in an online questionnaire designed to assess their understanding of EBPP, their familiarity with scientific platforms/databases, and their professional development investments. Latent class analysis (LCA) was conducted, which can be used to identify subgroups of psychologists with similar patterns of professional and training characteristics. Results: The results indicate that while psychologists recognized the importance of EBPP for effective patient care, there was a significant gap in understanding its fundamental principles and concepts. Many participants reported the limited use of scientific databases, missing opportunities to access the latest research advancements. A lower percentage of psychologists consistently implemented EBPP in their clinical practice, highlighting a gap between knowledge and application. Four latent classes emerged from the LCA: I—experienced/established professional psychologist; II—academic psychologist; III—supervised traditional psychologist; and IV—young professional psychologist. Conclusions: This study emphasizes the need for better integration of EBPP into psychology curricula and continuing education programs. Enhancing clinical psychologists’ understanding and proficiency in EBPP can promote evidence-based decision-making and improve the quality of mental health care in Brazil. Efforts should be made to familiarize psychologists with reliable scientific databases, equip them with skills to critically appraise research, and foster a culture of lifelong learning and professional development. Additionally, it is essential to develop strategies tailored to the distinct profiles of professionals identified in this study, considering their training sources, reference usage, and knowledge of EBPP.